Compliance, enablers and barriers to implementation of the cigarette and other tobacco products act, in Jodhpur, Rajasthan - Rai, Shubham; Joshi, Nitin Kumar; Jain, Yogesh Kumar; Saurabh, Suman; Bhardwaj, Pankaj (International Journal of Public Health Science (IJPHS), 2023)
Section 6 of the cigarette and other tobacco products act (COTPA) of India, lays down provisions and offences against tobacco sale to minors and near educational institutions. Considering well-documented violations and the significance of its better implementation, this study was planned to assess the knowledge and attitudes and compliance regarding provisions of COTPA section 6 among stakeholders, and identify potential enablers and barriers to implementation of the act. A cross-sectional study was conducted in ten senior secondary schools, two each from 5 zones of Jodhpur district. Principal and staff were interviewed to assess their knowledge and awareness, while a checklist was used to observe the compliance in the vicinity of schools. In-depth interviews were conducted amongst stakeholders to identify enablers and barriers. Only nine (45%) participants were aware about COTPA and six (30%) knew whom to report any violation. 60% schools had international “no smoking” signage and vendors were observed near 50% of the schools. Sale to minors was observed at two such stalls. Observed barriers were related to law and act, implementing personnel and community. Sensitisation of health hazards, intersectoral collaborations with prompt reporting might enhance compliance towards the law.